(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
The objective of the present study was to develop and optimize a buoyant tablet of Nateglinide to prolong the gastric residence time leading to reduce dose frequency which is an effective drug in the treatment of type II diabetes. The tablets were prepared by wet granulation technique using chitosan as a natural polymer in different ratios with sodium bicarbonate as gas generating agent. The compatibility of Nateglinide and all excipients were confirmed by FTIR spectroscopy. Pre-compression properties of granules are found within the prescribed limits and indicated good flow property. The tablets were evaluated for physical characteristics had shown that all of them comply with specifications of official pharmacopoeias. An optimized tablet formulation (F7) had less buoyancy lag time of 37 sec, total floating time of >12 hrs and higher the drug content of 100.16% and release of Nateglinide was 97.27 % after the end of 12 hours. From the kinetic modeling results, the drug release was Fickian diffusion controlled and followed zero order kinetics.